Integration of an Organic Rankine Cycle and a Photovoltaic Unit for Micro-Scale CHP Applications in the Residential Sector. (September 2017) - Settino, J.; Morrone, P.; Algieri, A.; Sant, T.; Micallef, C.; Farrugia, M.; Spitieri-Staines, C.; Licari, J.; Micallef, A.
Abstract: The purpose of this work is to analyse the performance of a novel system for combined heat and power (CHP) generation in small-scale applications. The system is based on an Organic Rankine Cycle (ORC) fed with biomass and a photovoltaic (PV) unit. The ORC and PV sub-systems operate in parallel to produce the required electrical energy. A preliminary investigation is performed to define the proper size of the photovoltaic unit. Afterwards, the analysis is focused on the hybrid system and a comparison between the two configurations is carried out. This work demonstrates the potential for integrating biomass and solar energy resources: during daylight, solar radiation is significant and the ORC system can be switched off or operated at partial load. Furthermore, the adoption of biomass makes it possible to overcome the intermittency of solar resource, increase the self-consumed electrical energy, and produce thermal energy, thereby saving natural gas for heating purposes.